Aspectos elementares e aplicações do cálculo com funções de variável complexa. - Sousa, Alana Cruz de (Universidade Federal do Tocantins, 2023)
The complex variable calculus has a large and complete basis compared to real variable calculus. By the way, this work applies the real variable calculus to the time independent Schrödinger equation. Some mathematical methods, as the Cauchy integral formula and residues theorem, have emphasis in this work, by essentially in the integration treatment that are analytical and with singularities. Our methodology involves the bibliographic study with algebraic and analytical situations related to complex systems. However, we noted that some solution techniques have important contributions not only in the solution development of proposed problems, but for important applications in the Mathematical Physics branch.